One high school basketball coach's self-study of leadership development. Issue 1 (2nd January 2017) - Mead, Jason; Gilson, Todd A.
Abstract: Over the course of one high school basketball season, a coach chronicled his journey as a mentor of his captains, leadership development and conducted a self-study on the data. Through field notes, interviews with captains, and journals, the coach described his successes and failures as a mentor in allowing captains to use their personal voice, distributing and delegating leadership tasks to captains, offering reminders of important leadership concepts, learning to mentor athletically skilled but quiet or inconsistent captains, and setting an effective example as the coach. Following the data presentation, a discussion regarding future research opportunities and practical applications for coaches is provided.